Memory changes following adjuvant temporo-parietal repetitive transcranial magnetic stimulation in schizophrenia - Gupta, Preeti (Indian J Psychiatry, 2021)
OBJECTIVE: The use of repetitive transcranial magnetic stimulation (rTMS) in schizophrenia has shown improvement as well as deficits in memory. Though most studies had focused on dorsolateral prefrontal cortex only, but impact of rTMS on cognitive functions remain inconclusive. The need of the study is to assess the impact of rTMS on memory in schizophrenia. MATERIALS AND METHODS: Forty right-handed male patients with schizophrenia were included by purposive sampling and rated on Positive and Negative Syndrome Scale (PANSS) before starting the rTMS treatment with the experimental group. Low frequency 1 Hz rTMS including 1200 stimulations were given over temporo-parietal cortex for 20 min as add on to medications. At the end of 10 session treatment (5 days a week for 2 weeks), the patients were re-evaluated. RESULTS: A total of 39 patients (20 for experimental group and 19 for control group) with mean age of 29.70 ± 9.05 and 31.26 ± 7.78 years, respectively, shows significant difference to pre- and post-treatment mean PANSS score in positive, negative and general psychopathology domains. The pre- and post-treatment mean Postgraduate Institute Memory Scale Scores with multivariate repeated measures analysis of variance revealed significant improvements in all memory domains (P < 0.01) except remote memory in both experimental and control groups. CONCLUSION: RTMS in combination with antipsychotics has shown improvement in psychopathology in patients of schizophrenia without any deterioration of memory.